Movement and Locality in Sundanese Wh‐Questions. (13th September 2012) - Davies, William D.; Kurniawan, Eri
Abstract : Abstract. Nominal wh ‐questions (nonprepositional arguments) in Indonesian‐type languages have received two principal analyses in recent years. Based on the three different surface strategies for forming these questions, Saddy (1991) has proposed distinct in situ, long‐distance‐movement, and partial‐movement analyses for Indonesian.Cole & Hermon (1998) adopt the same general proposal for Malay. Conversely, examining the three parallel structures, Davies (2003) has proposed that there is no interclausal wh ‐movement in Madurese but that all nominal wh ‐arguments are generated in situ. Sundanese presents the same basic structural options as the other three languages. Examining the grammatical characteristics of the long‐distance questions, we conclude that, as in Madurese, there is no evidence for interclausal A′‐movement in Sundanese and that the apparent cases of long‐distance movement are best analyzed as instances of A‐movement. These questions thus appear to share some characteristics of nominal wh ‐questions in other western Austronesian languages, such as Malagasy (Keenan 2008 ) and Tagalog (Gerassimova & Sells 2008 ).